PENGARUH INOVASI LINGKUNGAN, DUKUNGAN MANAJEMEN, BUDAYA ORGANISASI DAN INSENTIF TERHADAP GREEN EMPLOYEE INVOLVEMENT - Junaidi, Muhammad; Wahyuningsih, Yusminar; Martiah, Anisa; Partayasa, Ketut (Universitas Muhammadiyah Palembang, 2024)
Purpose– This research aims to investigate the role of Green Employee Involvement (GEI) in encouraging environmental innovation in companies. In a business context that is increasingly paying attention to sustainability, employee involvement in green initiatives is an important factor that can influence a company's ability to innovate in an environmentally friendly mannerDesign/methodology– This research uses quantitative methods by collecting data through questionnaires distributed to 250 employees from various companies that implement the Green HRM program. Data analysis was carried out through validity and reliability tests to ensure the reliability of the research instruments, followed by regression analysis to test the proposed hypotheses.Findings - These findings indicate that companies wishing to increase environmental innovation need to focus on increasing employee involvement in green initiatives, as well as ensuring there is strong management support and an organizational culture that supports sustainability